Factoring Trinomial

I would look for two factors of (3)(-4) = -12 whose sum is -4, which are 2 and -6:

(3x + 2y)(x - 2y)
 
So, even though this expression is not set up in the typical ax^2 + bx + c format, we can still use the factors of... that add to... method?
 
So, even though this expression is not set up in the typical ax^2 + bx + c format, we can still use the factors of... that add to... method?

I don't see why not. It's all the same behind-the-scenes, just hidden with a bit of "special effects." Consider the following values:

\(\displaystyle
a = 3 \\
b = -4y \\
c = -4y^2
\)
Then, we can examine the given polynomial:

\(\displaystyle 3x^2 - 4xy - 4y^2 \\
= (3)x^2 - (4y)x - (4y^2) \\
= (3)x^2 + (-4y)x + (-4y^2) \\
= ax^2 + bx + c
\)
 
Top